2018
DOI: 10.15666/aeer/1606_76697686
|View full text |Cite
|
Sign up to set email alerts
|

Requirements and Role of Selected Micro and Macro Elements in Nutrition of Cervids (Cervidae) - Review

Abstract: Cervidae are characterised by specific requirements for nutrients due to the structure of their gastrointestinal tract. The period of development of male antlers and lactation in females is associated with increased demand for protein, energy, and minerals. The paper presents the importance of Ca and P in cervid nutrition and the effect of these minerals on the health and ontogenic quality of these animals. The requirements for these macronutrients in relation to the age and sex of cervids as well as food avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(49 reference statements)
0
6
0
2
Order By: Relevance
“…Hemicellulose is important in terms of the ungulate diet; wild herbivores similarly process plant tissues with high concentrations of cellulose and hemicellulose (Capoani, 2019). Specifically, as sambar deer exhibit a well-developed gastrointestinal structure, they can use plant materials that are high in cellulose and hemicellulose, such as leaves, bark, and woody twigs; these are efficiently digested (Tajchman et al, 2018). Such materials are the principal ruminant fuels, typically providing up to 80% of energy (Barboza et al, 2009).…”
Section: Integrated Habitat Management; Habitat Suitability and Forag...mentioning
confidence: 99%
“…Hemicellulose is important in terms of the ungulate diet; wild herbivores similarly process plant tissues with high concentrations of cellulose and hemicellulose (Capoani, 2019). Specifically, as sambar deer exhibit a well-developed gastrointestinal structure, they can use plant materials that are high in cellulose and hemicellulose, such as leaves, bark, and woody twigs; these are efficiently digested (Tajchman et al, 2018). Such materials are the principal ruminant fuels, typically providing up to 80% of energy (Barboza et al, 2009).…”
Section: Integrated Habitat Management; Habitat Suitability and Forag...mentioning
confidence: 99%
“…The nutritional quality and concentrations of minerals in feed available in the environment may change without a predictable trend depending on the phenological phase of plants and between vegetation classes, types, and density structure [ 11 ]. It has been shown that the high variability in the concentrations of mineral compounds in plants depends on various components of plant cell walls, types of soil, precipitation rates, and weather conditions [ 11 , 12 ]. Wild cervids, unlike farmed representatives of this group of animals, are able to move freely and consume forest and cultivated plant species and can thus compensate for deficiencies in the intake of mineral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cervids, including deer, elk, and moose, are known to have a relatively high need for Ca, Na, and P, particularly for bone and antler formation and growth and during lactation (Carciofi & Saad, 2001; Hellgren & Pitts, 1997; Landete‐Castillejos et al., 2007; Tajchman et al., 2018). While these animals may have similar physiological needs to red brocket deer, each animal's needs are determined by deficiencies in their diet, and the red brocket deer's frugivorous diet varies from the grazing/browsing diets of most other cervids.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tested several of those interactions: Mg (and Ca) and P, Cu and Fe, Fe and Mn, and Cu and Zn. All of these interactions appeared in the optimal model and are known to interact in the digestive systems of ruminants (Tajchman et al., 2018) which indicates that simple comparisons between consumed and control soils are too simplistic to draw conclusions from, and more complex statistical methods are needed. The influence of potential toxicity could be tested with a large enough sample size by including polynomial terms in models of geophagy.…”
Section: Discussionmentioning
confidence: 99%